2011
DOI: 10.1021/la104726w
|View full text |Cite
|
Sign up to set email alerts
|

Unique Properties of Bubbles and Foam Films Stabilized by HFBII Hydrophobin

Abstract: The HFBII hydrophobin is an amphiphilic protein that can irreversibly adsorb at the air/water interface. The formed protein monolayers can reach a state of two-dimensional elastic solid that exhibits a high mechanical strength as compared to adsorption layers of typical amphiphilic proteins. Bubbles formed in HFBII solutions preserve the nonspherical shape they had at the moment of solidification of their surfaces. The stirring of HFBII solutions leads to the formation of many bubbles of micrometer size. Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
87
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 69 publications
10
87
0
Order By: Relevance
“…[5] We have investigated HFBII as am icrobubble shell component for medical US imaging. Another consequence of HFBII monolayers being in as olid state is that millimetric [8] and micrometric [9] HFBII-stabilized bubbles adopt elongated shapes.D ispersions containing both elongated and spherical microbubbles are suboptimal as USCAs ince microbubble resonance frequency depends on the radius. [6] While microbubble stability is essential for use as USCA, excessive elasticity is expected to shift the bubbles resonance frequencyt oh igh values [7] that may exceed those commonly used in radiology (that is,f rom 2t o1 5MHz).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] We have investigated HFBII as am icrobubble shell component for medical US imaging. Another consequence of HFBII monolayers being in as olid state is that millimetric [8] and micrometric [9] HFBII-stabilized bubbles adopt elongated shapes.D ispersions containing both elongated and spherical microbubbles are suboptimal as USCAs ince microbubble resonance frequency depends on the radius. [6] While microbubble stability is essential for use as USCA, excessive elasticity is expected to shift the bubbles resonance frequencyt oh igh values [7] that may exceed those commonly used in radiology (that is,f rom 2t o1 5MHz).…”
mentioning
confidence: 99%
“…[6] While microbubble stability is essential for use as USCA, excessive elasticity is expected to shift the bubbles resonance frequencyt oh igh values [7] that may exceed those commonly used in radiology (that is,f rom 2t o1 5MHz). Another consequence of HFBII monolayers being in as olid state is that millimetric [8] and micrometric [9] HFBII-stabilized bubbles adopt elongated shapes.D ispersions containing both elongated and spherical microbubbles are suboptimal as USCAs ince microbubble resonance frequency depends on the radius. [10] Finally,s ome feasibility tests showed that dispersing HFBII and preparing microbubbles using standard procedures leads to heterogeneous mixtures consisting largely of micron-sized aggregates along with both spherical and elongated microbubbles (see below), thus impeding the reproducible and effective formation of echogenic microbubbles.…”
mentioning
confidence: 99%
“…When it comes to self‐assembly at the interface, surface activity of HPBs (Class II) is higher than other common food proteins (such as β‐lactoglobulin, β‐casein, whey protein isolates, and sodium caseinates), instead of unfolding at the interface like typical globular proteins, they self‐assemble to form a highly coherent viscoelastic layer due to the association of molecules in the lateral direction . Moreover, the solid‐like interfacial character (surface shear elasticity) is acquired much faster than with other common food proteins . This basically implies that HPBs diffuse rapidly to the interfaces, where they hold a globular shape while also self‐associating into elastic films.…”
Section: Starting Materials For Fabricating Functional and Engineeredmentioning
confidence: 99%
“…It deserves also mention Dr. Karin Scholtmeijer as a researcher from the same group with many publications Class II HFBI (10 mg/mL, purity of 68 %) Efficient purification of endoglucanase [80] Class I SC3 (300 lg/mL) Immobilization of glucose oxidase and horseradish peroxidase [81] Class I SC3 (30 lg/mL) Polymer surface modification [82] Class II HFBI (100 lg/mL) Glass surface modification [83] Class II HFBI (211 mg/mL, purity of 99 %) Potential fusion partner for one step purification of avidin from insect cells [84] Class II HFBII (1 mg/mL) Stabilization of bubbles and foams [53] Class I SC3 (40 lg/mL) Formulation of water insoluble drugs for oral administration [85] Class II HFBI (500 lg/mL) Coating of drug nanoparticle [78] Class II HFBI (20 lg/mL) Dispersion multi walled carbon nanotubes [86] about surface modification by hydrophobin [15,114,115] and other aspects [116]. [117,[120][121][122].…”
Section: Institute Of Biomembranes-utrecht University In Collaboratiomentioning
confidence: 99%